Skuteczność latanoprostu w jaskrze wieku dziecięcego - Urban, Beata; Bakunowicz-Łazarczyk, Alina; Mrugacz, Małgorzata; Oziębło-Kupczyk, Monika (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
Latanoprost is a prostaglandin F2α analog that reduces intraocular pressure by 20-40% in adults with open-angle glaucoma. The efficacy and safety of this drug in children has not been widely reported. In our study we evaluated the effect of latanoprost in 14 children aged 12-18 years (mean 15 years): 10 patients with glaucoma juvenile (I group); 2 patients with secondary glaucoma because of uveitis recidivans and 2 patients with aniridia and albinismus (II group). In the I group the average IOP decrement was 9 mmHg or 36,5% (range 29-44%). In the II group the average IOP decrement was 6,5 mmHg or 23,5% (range 11-33%). In one child with aniridia after one year of treatment IOL rose again to 26 mmHg and antiglaucomatous surgery was necessary. Ocular side effects in children of latanoprost are mild.